Unhygienic practices of health professionals in Brazilian public hospital restaurants : an alert to promote new policies and hygiene practices in the hospitals - Draeger, Cainara Lins (2019)
This study aimed to evaluate health professionals’ unhygienic practices and the stages of behaviour change in Brazilian public hospital restaurants. We evaluated all medium/large-sized public hospital restaurants (HRs) from the Brazilian Federal District (n = 9); a representative sample of 128 users). We evaluated the HRs’ physical structures, their consumers’ socio-demographic characteristics, their unhygienic practices, as well as the stages of behavioural change concerning unhygienic practices. All the HRs presented their menus for self-service distribution, so customers entered in lines to serve themselves. All the HRs had hand-wash sinks for customers; 77.8% offered antiseptic liquid soap; 33.3% offered alcohol gel; and 77.8% offered storage for professional accessories before serving food. Almost half (46.8%) of the customers did not sanitise their hands (with water and antiseptic soap and/or use of alcohol gel) immediately before serving, and 24.2% wore professional uniforms at HRs. Almost half (43.5%) of the customers spoke with each other in line while serving their plates and arranged the food on their plates with the serving utensils from the distribution counter. The declaration of behavioural change was inversely associated with the hygiene practices. Almost half of the individuals did not sanitize their hands; however, 90.4% declared “changed behaviour” when this contaminant practice was presented to them. We verified a high percentage of hygiene practices inconsistent with most of the customers´ answers about their stage of behaviour change. Based on the observations of this study, it is necessary for an awareness program to be developed that is focused on customers of HRs in order to reduce unhygienic practices. Also, it is important to promote new policies for proper hygiene practices in hospital restaurants.